Night Illumination-Niche in the Court of Four Seasons (Souvenir Guide Publishers)
Note On verso: The Court of the Four Seasons is one of the chief beauty spots of the Exposition. It was designed by Henry Bacon, of New York. The architecture is Italian Renaissance style, Hadrian's Villa, one of the historic Roman palaces, being accredited as the inspiration.